About coincidence points theorems on 2-step Carnot groups with 1-dimensional centre equipped with Box-quasimetrics - Alexander Greshnov; Vladimir Potapov (AIMS Mathematics, 2023)
For some class of 2-step Carnot groups $ D_n $ with 1-dimensional centre we find the exact values of the constants in $ (1, q_2) $-generalized triangle inequality for their $ \text{Box} $-quasimetrics $ ρ_{\text{Box}_{D_n}} $. Using this result we get the best version of the Coincidence Points Theorem of $ α $-covering and $ β $-Lipschitz mappings defined on $ (D_n, ρ_{\text{Box}_{D_n}}) $.